“ANGER” METAFORASINING MATNDA FAOLLAShUVI - Kalimbetov, Sh.M. (SCIENCE and SOCIETY, 2025)
This article analyzes the practical and theoretical aspects of the activation of conceptual metaphor in the text, which is one of the current issues. The article focuses on conceptual metaphors related to the emotional concepts of anger and the expressions that provide their linguistic occurrence.